Comparison of GFAP and HSP27 concentrations in acute moderate-intensity aerobic exercise of different duration (Medical Journal of Indonesia, 2016)
Background: Glial fibrillary acidic protein (GFAP) and heat shock protein -27 (HSP27) plasma can be used as the parameters of exercise-induced astrocyte reactivity. The American College of Sports Medicine (ACSM) recommends an exercise of 30 minutes or 10 minutes duration (each performing bout accumulated toward 30 minutes). The aim of this study was to compare GFAP and HSP27 plasma concentrations in young adults undergoing acute moderate-intensity aerobic exercise of different durations (10 minutes vs 30 minutes).Methods: An experimental study with pre-post design was conducted on 22 participants assigned to either 10 minutes or 30 minutes duration of single bout exercise. Blood sampling was performed before and after the exercise. GFAP and HSP27 plasma levels were measured with ELISA methods. Plasma GFAP and HSP27 levels before and after exercise were analyzed using paired t -test, while GFAP and HSP27 levels after exercise between the two groups were processed using unpaired t-test.Results: Plasma GFAP concentration decreased significantly (0,45 ng/mL) after 30 minutes of aerobic exercise (p<0.05). Plasma HSP27 concentration decreased significantly (1,71 ng/mL) after 10 minutes of aerobic exercise (p<0.05). No significant difference in plasma GFAP and HSP27 concentrations between 10 minutes (GFAP=0.49 ng/mL; HSP27=2.09 ng/mL) and 30 minutes duration of exercise (GFAP=0.45 ng/mL; HSP27=1,71 ng/mL).Conclusion: Acute moderate-intensity aerobic exercise with 10- and 30-minutes duration reduces the reactivity of astrocytes indication the increase of the synapse plasticity. The decrease in GFAP concentration occurred after 30 minutes of exercise and the decrease in HSP27 occurred after 10 minutes of exercise. These results showed that the body responds differently to different treatment duration in order to obtain the same effect on the body.